Evaluated density estimates of young forest stands using high resolution 2D imagery from UAV - Kingstad, Victor (2020)
After more than three decades of advanced technology and methods to evaluate young forest attributes, the forestry still prefers laborious field surveys in regenera-tion forests. Preceding studies have virtually all successfully identified the saplings, but the cost has outweighed the benefits or at least not yet convinced the companies to step away from the traditional field surveys; high-resolution photogrammetric point clouds and ALS-data can provide accurate estimations of the biophysical prop-erties but requires intense data processing. One way to reduce the costs could be to use less accurate 2D imagery by scaling images to the approximate altitude. The fundamentals of using cheap low-tech UAV imagery to aid management of young boreal forests was explored in this study, the results were obtained by com-paring image interpreted saplings from images processed by Dianthus Rapid Drone Map™ to Sveaskog’s traditional inventory practices of young forest stands. Three main issues were evaluated: ‘Camera positioning and image scale’, ‘Sapling classifi-cation’ and ‘Need for cleaning assessment’. The study area included 57 forest stands and 290 sample plots within the county of Västerbotten, northern Sweden. The ma-terial & methods in the study were mainly predetermined by available equipment and field instructions from Sveaskog to enable efficient data collection through combined labour- and research work. The results revealed that manual interpretation of the acquired images could dis-criminate between forest stands in need of cleaning and not with 82% accuracy, though the individual sapling counts comprised large errors, (Overall RMSE 6568 stems ha-1). Possible advantages compared to traditional surveys are the production of up to date high-quality maps for the brush-cutter operators, improved planning of retention delineation and most of all reduced time spent in field since over 1 million hectares are estimated in need of cleaning in Sweden annually. This study indicated that simple UAV imagery without proper photogrammetry could be an alternative; the quality might be bad but possibly sufficient.